2020
DOI: 10.1186/s40494-020-0363-x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of Liu Kang’s palette and the discovery and interpretation of hidden paint layers

Abstract: This paper presents an overview of the results from the ongoing study on the materials and painting technique of the pioneering Singapore artist-Liu Kang. The paintings Zuo La Lu and Nude, which represent two of Liu Kang's early and distinct artistic phases-Paris and Shanghai-were investigated for the first time using a combination of non-and micro-invasive techniques. The aim of this study was to identify the main pigments used by the artist and to add to the existing research on the artist's painting methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…NIR imaging also did not aid in visualising the underlying composition, probably due to the thickness of the current paint layer. Nevertheless, the discovery of different paint scheme is not a unique occurrence in Liu Kang's artworks and is consistent with his earlier practice of reusing former paintings in Paris and Shanghai (Lizun, 2020;Lizun et al, 2021a;2021b;2021c). (Liu, 1993).…”
Section: Non-invasive Examination Of Climbing the Hillsupporting
confidence: 78%
See 1 more Smart Citation
“…NIR imaging also did not aid in visualising the underlying composition, probably due to the thickness of the current paint layer. Nevertheless, the discovery of different paint scheme is not a unique occurrence in Liu Kang's artworks and is consistent with his earlier practice of reusing former paintings in Paris and Shanghai (Lizun, 2020;Lizun et al, 2021a;2021b;2021c). (Liu, 1993).…”
Section: Non-invasive Examination Of Climbing the Hillsupporting
confidence: 78%
“…and Shanghai (1932)(1933)(1934)(1935)(1936)(1937) artistic phases (Lizun et al, 2021b). Moreover, some references were made to the earlier research about Liu Kang's painting practice (Lizun, 2020;Lizun et al, 2021a;Lizun et al, 2021c). An additional insightful search of the Liu family archives provided unexpected evidence, which combined with the analytical techniques, assisted in determining the provenance and dating of Climbing the hill.…”
mentioning
confidence: 99%
“…Larger painting supports (number 12 and 20), were used sparingly. Financial constraints could also have had an impact on the artist's choice of materials [14]. Therefore, it is worth noting that 11 paintings were created over rejected compositions and four on the reverse side of earlier paintings.…”
Section: Auxiliary Supports and Canvas Formatsmentioning
confidence: 99%
“…The evidence collected from 15 paintings created in Paris confirmed that artist did not mind reusing his earlier compositions or utilising their reverse sides if he was short of painting supports. These paintings were created without the application of an intermediate ground layer [14]. Hence, it could be possible that Liu Kang had seen a few, rare, examples of such an approach among Impressionist and Neo-impressionist painters [16], whose works influenced his own [13].…”
Section: Characteristics Of the Groundsmentioning
confidence: 99%
See 1 more Smart Citation